Considerations for Testing and Treating Children with Central Vestibular Impairments - Christy, Jennifer B. (Seminars in Hearing, 2018)
This perspective explores common pediatric diagnoses that could present with central vestibular pathway dysfunction, leading to delays in motor development and postural control, and gaze instability. Specifically, the following diagnoses are considered: cerebral palsy, myelomeningocele, vestibular migraine, attention-deficit hyperactivity disorder, developmental coordination disorder, concussion, childhood cancer, congenital muscular torticollis, adolescent idiopathic scoliosis, and autism. Suggestions for clinical screening, vestibular function testing, and vestibular rehabilitation for children with these diagnoses are based on evidence for the efficacy of testing and interventions for children with peripheral vestibular hypofunction. More research is needed to explore peripheral and central vestibular function in children with these diagnoses. Testing and intervention methods may need to be modified to accommodate for the specific behavior and motor challenges that some children might present. Researchers should develop technology so that gaze stabilization exercises can be delivered in a fun, functional, and effective way.
Keywords: central vestibular system; vestibular rehabilitation; pediatrics